1998
DOI: 10.1289/ehp.9810661
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and sex of children and the correlation to the body burden of PCDDs/PCDFs and PCBs of the mother.

Abstract: Polyhlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and polychlorinated biphenyis (PCBs) were analyzed in 167 random human milk samples from urban and rral areas in Finland. Dietary habits and background information on each mother and child were gathered by questionnaire. Body mass indexes (BMI) before pregnancy and delivery in the mral area were 5-10% higher than in the urban area, but fat content of mother's milk was about 10% higher in the urban area. The mean weights of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
50
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 15 publications
13
50
4
Order By: Relevance
“…Similar to our study, several previous studies have found no significant association between the concentration of PCBs in milk samples and birth weight of primiparas (Rogan et al, 1986;Vartiainen et al, 1998) or head circumference (Rogan et al, 1986). Several studies which have measured fetal exposure to PCBs by maternal fish intake from contaminated waters did not find associations between high intake of PCBs in the mother and miscarriage (Axmon et al, 2000), stillbirth (Axmon et al, 2000;Rylander et al, 2000), spontaneous fetal death (Mendola et al, 1995) or congenital malformations .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to our study, several previous studies have found no significant association between the concentration of PCBs in milk samples and birth weight of primiparas (Rogan et al, 1986;Vartiainen et al, 1998) or head circumference (Rogan et al, 1986). Several studies which have measured fetal exposure to PCBs by maternal fish intake from contaminated waters did not find associations between high intake of PCBs in the mother and miscarriage (Axmon et al, 2000), stillbirth (Axmon et al, 2000;Rylander et al, 2000), spontaneous fetal death (Mendola et al, 1995) or congenital malformations .…”
Section: Discussionsupporting
confidence: 87%
“…Our measures were less than some similar previous studies using breast milk for PCB contamination measurement (Rogan et al, 1986;Schade and Heinzow, 1998;Vartiainen et al, 1998).…”
Section: Discussioncontrasting
confidence: 65%
“…The levels of PCDDs/PCDFs and DL-PCBs in maternal blood during pregnancy more directly evaluate the fetal exposure levels than those levels in breast milk. Our study is the first to report the influence of the levels of PCDDs/PCDFs and DL-PCBs in maternal blood on birth weight, although Vartiainen et al, Tajimi et al and Nishijo et al have studied the effects on birth weight using those levels in breast milk (Vartiainen et al, 1998;Tajimi et al, 2005;Nishijo et al, 2008). We also examined which individual congeners of PCDDs/PCDFs and DL-PCBs have harmful effects on birth weight.…”
Section: Discussionmentioning
confidence: 91%
“…The influence of low-level exposure to PCDDs/PCDFs and DL-PCBs on birth size has not been reported as frequently as exposure to organochlorine pesticides and PCBs. A Finnish study reported that birth weight, especially of boys, correlated negatively with TEQ levels of PCDDs/PCDFs in breast milk (Vartiainen et al, 1998). Another recent study examining the effects of individual congeners of PCDDs/PCDFs and DL-PCBs on birth weight reported that only OCDD levels in breast milk had a significant negative correlation (Tajimi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation